If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-19-3(x-2)=3(4-x)
We move all terms to the left:
x-19-3(x-2)-(3(4-x))=0
We add all the numbers together, and all the variables
x-3(x-2)-(3(-1x+4))-19=0
We multiply parentheses
x-3x-(3(-1x+4))+6-19=0
We calculate terms in parentheses: -(3(-1x+4)), so:We add all the numbers together, and all the variables
3(-1x+4)
We multiply parentheses
-3x+12
Back to the equation:
-(-3x+12)
-2x-(-3x+12)-13=0
We get rid of parentheses
-2x+3x-12-13=0
We add all the numbers together, and all the variables
x-25=0
We move all terms containing x to the left, all other terms to the right
x=25
| 3*(2-3*x)=6 | | 3*y=15-7*(y+3) | | 5*(x+4)=4*(x-4) | | 2(4w)+2w=560 | | 5(2x+4=8(x-3) | | 14x-3x=171 | | 5/10-3x=30/10 | | 3(4x-7)=10(x+50) | | 3(4x-7=10(x+50) | | 3(4x-7=10(x+50 | | 5.5x=75 | | 2y/7=-24 | | 13-2x-10=5x+3 | | 4.8x-3.8x^2=0 | | 3/4^x+2=27/64^4-3x | | -12x=-45 | | 3(a-2)+2=24 | | x+7+3x=53 | | 5.2-y=-5.5 | | 16.4=16t^2+24t | | 2(x+1)-1=2(x-3)+7 | | -6-2(x-6)=-3x+6(x-4) | | 100+4x=80 | | f(x)=7x+28x+21 | | m+9m+9=19 | | 1=(2(t+13))/(10+t) | | 50=5x-3+7x+7 | | 14.69+0.06x+0.18=15.44-0.15x | | 9x-4x+116=9x+76 | | 15.11+0.11m=15.61-0.16m | | 15/5=6u | | -32+x=60 |